Topical and systemic therapies in melasma: A systematic review - Rashmi Sarkar; Evangeline B Handog; Anupam Das; Anuva Bansal; Ma Juliet Macarayo; Vinay Keshavmurthy; Vignesh Narayan; Soumya Jagadeesan; Eugenio Pipo III; Grace Monica Ibaviosa; Indrashis Podder; Shivani Bansal (Wolters Kluwer Medknow Publications, 2023)
Introduction: Melasma is an acquired disorder, which presents with well-demarcated, brown-colored hyperpigmented macules, commonly involving the sun-exposed areas such as the face. It is a chronic and distressing condition, affecting the patients' quality of life, and has been conventionally treated with "first-line" agents including hydroquinone (HQ) alone or as a part of a triple combination cream (TCC), while "second-line" options include chemical peels, and third line options include laser therapy. Materials and Methods: A systematic search was performed for all topical and systemic treatments for melasma up till May 4, 2021, using the PubMed and EMBASE databases, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The search terms "melasma" and "treatment" were used to search for the relevant articles on both these databases, and a total of 4020 articles were identified. After removing the duplicate entries and screening the titles, abstracts, and full-text articles, we identified 174 randomized controlled trials (RCTs) or controlled clinical trials. Results: Based on our review, HQ, TCCs, sunscreens, kojic acid (KA), and azelaic acid receive grade A recommendation. Further large-scale studies are required to clearly establish the efficacy of topical vitamin C, resorcinol, and topical tranexamic acid (TXA).Several newer topical agents may play a role only as an add-on or second-line drugs or as maintenance therapy. Oral TXA has a strong recommendation, provided there are no contraindications. Procyanidins, Polypodium leucotomos (PL), and even synbiotics may be taken as adjuncts. Discussion: Several newer topical and systemic agents with multimodal mechanisms of action have now become available, and the balance seems to be tipping in favor of these innovative modalities. However, it is worth mentioning that the choice of agent should be individualized and subject to availability in a particular country.